KARUT-MARUT PARTAI POLITIK DALAM PENTAS POLITIK DI TINGKAT LOKAL - Efriza . (Universitas Nasional, 2016)
This article discusses the behavior of political parties in elections at the local level that indicates the failure of the party in exercising leadership recruitment. According to the authors, political parties in Indonesia has pursued a policy of pragmatic and ignore the ideology of the party in nominating candidates for regional heads, so that the present is the attitude minus the ethics of political parties, the oligarchs at the local level and the political inheritance electoral impact neglect of elections as the provision of stock of the national leadership. This study found that operation elections became chaotic by the behavior of the party's failure to carry out roles and functions of such recruitment. The theory is applied perspective is a Political Party System and Political Parties, and Nomadism Party; to understand the concept of the behavior of political parties in the political arena local level.